Simulation Method: A Breakthrough to Improve Understanding of Fiqih Materials - Pajar Sidik; Nurmia Suhartini; Mita Purnamasari; Imam Tabroni (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to identify and analyze the application of simulation methods in Fiqh Learning for students at MAN Purwakarta, which included the application of simulation methods in fiqh learning for students, the process of simulation methods carried out by teachers, effective simulation methods used by teachers, using qualitative methods. In analyzing the data, the researcher used qualitative analysis techniques with the process of reducing data, presenting data and drawing conclusions. From the results of this study: That the application of the simulation method in learning fiqh to students at MAN Purwakarta is very effectively applied, because the application of the simulation method improves students' understanding and learning outcomes in fiqh learning. The simulation method is very effectively applied in fiqh learning, this is reflected in the attitude of students who are very enthusiastic about the application of simulation methods and the application of simulation methods in fiqh learning is more helpful for students in understanding the implementation of worship.